282 ASSOCIATION BETWEEN PESTICIDE METABOLITE LEVELS AND EXPOSURE FROM THE HOME AND DIET. Issue 1 (1st January 2007) - Roberts, J. R.; Reigart, J. R.; Hulsey, T. C.
Abstract : Objective: To evaluate the association between measured metabolites of organophosphate (OP) and pyrethroid metabolite levels and indicators of exposure through home and diet. Methods: Data from the 2001-02 National Health and Nutrition Examination Surveys (NHANES) were used to evaluate exposure to pesticides in the US population. Questions included use of pesticides in the last month, types of treatment done (home, yard, foundation), whether performed by a professional or nonprofessional, and the number of rooms treated. Nutritional questions included intake of different foods and participation in the WIC program. Lab data consisted of urinary metabolites of OP and pyrethroid insecticides. Data were imported into SAS and analyzed using SAS callable SUDAAN . Age for all variables was limited to 6 years or older to maintain consistency with ages of participants for lab data. A new variable was created for total OP metabolites to assess cumulative exposure. Frequencies were determined and continuous variables were compared with t -tests and ANOVA. Appropriate 2-year weights were used to create a representative US sample. Results: The 3, 073 surveys comprise a representative sample of 50, 704, 925 US children ages 6 to 18 years. Eighteen percent reported using pesticides in the home in the last month and 20% reported treatment in the yard. Seventy-four percent of respondents reported having a nonprofessional treat the home, and 32% of respondents reported having a professional treat the home. Half of families had one room treated, whereas 13% had at least three rooms treated. Mean residues of all OP and pyrethroid metabolites were significantly higher in homes that were treated in the past month, with the exception of chlorpyrifos, which was lower. All metabolite levels except parathion were significantly higher when a nonprofessional treated the home compared with professional treatment. Of note, pyrethroid metabolites were four times higher in the home treated by nonprofessionals. Metabolite levels were also significantly higher when a nonprofessional treated the yard as opposed to the professional; pyrethroid metabolites were two times higher, and total OP levels were three times higher. Total OP levels were higher with daily intake of greens and dried beans/peas compared with no intake. There was no correlation with eating out in restaurants and pesticide metabolites. OP and pyrethroid metabolites were higher as the number of school lunches eaten per week increased. Conclusions: Urinary metabolites of pesticides are higher when pesticides have been applied in the last month and when applied by a nonprofessional. Certain dietary exposure may increase pesticide metabolites, although the effect seemed less pronounced than from home or yard treatment. Due to the cross-sectional nature of NHANES, these data need confirmation using prospective study methods.